(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the association between the neutrophil-to-lymphocyte ratio (NLR) and the clinical characteristics of patients with chronic hepatitis B virus-related hepatocellular carcinoma (HBV-HCC). Methods: A cross-sectional descriptive study was conducted on 100 patients diagnosed with HBV-HCC. Results: The NLR was significantly higher in patients with Child-Pugh class B and C compared to those with Child-Pugh class A (p = 0.004). HBV-HCC patients with a larger maximum tumor size exhibited a higher NLR (p = 0.0013). Furthermore, hepatocellular carcinoma patients with portal vein thrombosis had a significantly higher NLR than those without thrombosis (p = 0.023). Additionally, the NLR was elevated in subgroups presenting with weight loss (p = 0.0029), mucocutaneous jaundice (p = 0.0445), and collateral circulation (p = 0.0216). Conversely, there were no significant differences in the NLR among subgroups stratified by tumor number, metastasis status, or cancer stage. Conclusion: A higher NLR is observed in HBV-HCC patients presenting with Child-Pugh class B and C, larger tumor sizes, portal vein thrombosis, weight loss, mucocutaneous jaundice, and collateral circulation. The NLR is not associated with cancer stages, metastasis, or the number of tumors.